ANALYSIS OF INDUSTRIAL PRACTICE OF DRUG QUALITY RISK MANAGEMENT IN RUSSIAN PHARMACEUTICAL ENTERPRISES - A. B. Kashirina; Zh. I. Aladysheva; N. V. Pyatigorskaya; V. V. Belyaev; V. V. Beregovykh (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2021)
The aim of the research was to study the current industrial practice of drug quality risk management in Russian pharmaceutical enterprises, including the assessment of the main problems during the implementation of the risk management system and its compliance with the accepted international approaches.Materials and methods. In the period from 6 April to 10 May 2020, an online survey of the leading employees in the field of quality assurance of Russian manufacturers was conducted. In the survey, the questionnaire was based on the results of the authors' analysis of the national regulatory legal acts of the Russian Federation, the European Union countries, international guidelines of the EAEU, ICH and WHO in this area. 111 people took part in the survey, the return of questionnaires was 11.5%.Results. The data obtained indicate the prevalence of a superficial approach to quality risk management in the Russian pharmaceutical industry, the presence of objective and subjective reasons that hinder the effective implementation of these methods, the fragmentation of the systems used and, in most cases, their ineffective use. The respondents believe that the most significant reasons for the difficulties in implementing this methodology, are the lack of recommendations from the Ministry of Industry and Trade of Russia on creating an effective quality risk management system and a shortage of the specialists who are ready to work in the area of this industry. The survey revealed rather large gaps in the deployment of a risk management system at the enterprise and separation from the established international practice.Conclusions. The data obtained indicate the extreme urgency of developing recommendations for a quality risk management system, which should be based upon and supported by Russian regulatory legal acts and international experience in this area. The authors propose highlights for these recommendations.